Stres Akademik Mahasiswa di Sekolah Tinggi Ilmu Kesehatan Santa Elisabeth Medan - Ance Siallagan; Agustaria Ginting; Bella Mayta Tindaon (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
Stress is a body reaction in the form of symptoms and signs of pressure resulting from a mismatch in one's ability to adapt to an environment that exceeds one's limits. Stress is caused by external and internal factors. Stress can lead to decreased endurance, cardiovascular disorders, mental decline, bad behavior and can even lead to suicide. The purpose of this study was to identify the level of academic stress of first semester students at STIKes Santa Elisabeth Medan in 2022, a total of 159 people. The results showed that students who experienced academic stress were in the high category by 6.9%, the medium category by 91.2%, and the low category by 1.9%. Students are expected to be able to overcome academic stress by applying adaptive coping mechanisms such as socializing or sharing with peers or people they trust, exercising regularly, praying individually or together.